Development of the Cost and Time Estimation Factors of the Project Dimension in the Agile Software - Govil, Nikhil; Sharma, Ashish (Iraqi Journal of Science, 2023)
Agile methodologies are adopted extensively by many of the software industries as it is flexible in nature as well as can address the required changes in any phase of development. Authentic estimation of the software products is not an easy task as it requires continuous attention of the product owner. Effort and cost can be estimated in a proper manner to ensure the success of the project. In this article, we considered the Scrum-based Agile projects that are developed into several Sprints. We proposed an extension to an existing algorithm, based on a total of 36 success factors; that estimate the development cost and effort required to complete the project. For estimation and computations, we have taken a dataset of 12 projects that are validated through experienced professionals. We also compared our results with the existing approach and it is found that our results are cost-effective even after considering more success factors.